Flexibility of Work in Employment Relations and Labour Deployment in the Nigeria Labour Market - Idowu, Taofik; Ilesanmi, Ayodeji; Oyetunde, Kabiru (Al Tijarahh, 2020)
The paradigm shift in the world of work has created a new dimension in the labour market vis a vis employment relation; a point of reference is the flexibility of work and labour deployment in the Nigeria labour market. The study examines flexibility of work in employment relations and deployment of labour in the Nigeria labour market within the purview of relationship and the benefits to the employers and employees. Hence, the study takes an exploratory approach by reviewing extant literatures to understand the dynamics of work flexibility in employment relations and its influence on different patterns of labour deployment. The findings from the review of extant literatures revealed that there are various dimensions to flexibility of work in employment relations(workplace flexibility, workforce flexibility, low flexibility and mutual flexibility) and labor deployment(temporary worker, part time workers triangular employees etc.) in the Nigeria labour market and itÂ oftenÂ benefit the employer more because of the objective of maximizing return on investment by creating financial rigidity on the employee through cutting or reduction in the personnel cost or overhead cost. This study therefore recommends that a win-win flexible work dimension for deploying of workers for flexible work arrangement should be adopted to achieve a healthy employment relations practice in the Nigeria labour market.